Presentations : best practices vs. what's practiced - a field research. - Chan, Michelle Pui Teng. (2008)
This paper explores how Powerpoint Presentations are given in business settings in Singapore, and aims to identify the gaps, if any, between actual business practices and best practices. The significance of this gap is also examined.